Kepastian Hukum Sertipikat Hak Atas Tanah dengan Dasar Penerbitan Surat Palsu (Studi Putusan Pengadilan Negeri Batusangkar Nomor 67/Pid.B/2021/PN Bsk) - Yodi Nugraha; Rembrandt Rembrandt; Syofirman Sofyan (LPPM Universitas Ekasakti Padang, 2023)
The case of a land dispute with the object of the dispute being a certificate of land rights issued using a fake document is the Decision of the Class II Batusangkar District Court Number 67/Pid.B/2021/PN Bsk which has obtained permanent legal force. The dispute in this case is located in Jorong Baruah, Nagari Padang Magek, Rangkat District, Tanah Datar Regency. The research method used is normative juridical with a case approach. The findings in this research, namely that certificates of land rights issued using fake documents, certainly do not provide legal certainty. This certificate can be categorized as a genuine but fake certificate. This kind of certificate must of course be canceled and declared invalid and withdrawn from circulation after being proven through a process in the District Court. To prevent the occurrence of genuine but fake certificates, this is by increasing the accuracy of the authorities who process the creation and issuance of land title certificates. The consideration of the Panel of Judges in the Decision of the Batusangkar District Court Number 67/Pid.B/2021/PN Bsk is that the Defendant was legally and convincingly proven at trial to fulfill the criminal elements charged by the Public Prosecutor, namely Article 263 paragraph (1) of the Criminal Code. So the Panel of Judges sentenced the Defendant to imprisonment for 1 (one) year and 6 (six) months.